Magnetic materials and 3D finite element modeling - Bastos, Joô Pedro Assumṗô; Sadowski, Nelson (CRC Press, 2014)
This book provides the necessary information on material characterization and finite element methods applications. It begins with a thorough introduction to materials and basic electromagnetics, and provides a refresher on the finite elements method concepts. The book then moves into experimental and numerical modeling related to losses and material characterization with an emphasis on hysteresis. The second half of the book employs the concepts of the material characterization chapters by focusing on the finite elements method applied to 3D applications